2003
DOI: 10.7589/0090-3558-39.1.203
|View full text |Cite
|
Sign up to set email alerts
|

Blood Parasites in Sage-Grouse From Nevada and Oregon

Abstract: Peripheral blood smears from 196 adult and yearling female greater sage-grouse (Centrocercus urophasianus) were examined for blood parasites (167 from the breeding and 29 from the brood-rearing season) to determine prevalence of blood parasites, to attempt to correlate infection with chick survival, and to establish base-line values of prevalence in sage-grouse from Nevada and Oregon (USA). Birds were captured and released on two study areas during 1999-2001; Sheldon National Wildlife Refuge (SNWR) in northwes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Maejohnen-dake. Infection of the ptarmigan and the grouse with this parasite was observed across a wide-range of their habitat in both Nearctic and Palearctic regions [6,11]. In our study, we clarified that these hematozoa were distributed widely throughout the northern and southern populations of the ptarmigan in the Japanese Alps (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…Maejohnen-dake. Infection of the ptarmigan and the grouse with this parasite was observed across a wide-range of their habitat in both Nearctic and Palearctic regions [6,11]. In our study, we clarified that these hematozoa were distributed widely throughout the northern and southern populations of the ptarmigan in the Japanese Alps (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…One of the major impacts of infection with Leucocytozoon in other species of birds is a decrease in reproductive performance (Merino et al 2000;Dunbar et al 2003). There was no evidence to suggest that Leucocytozoon played a significant role during the 2008-2009 breeding season on the Otago Peninsula.…”
Section: Discussionmentioning
confidence: 98%
“…Although the effects of L. lovati to host birds have not been elucidated yet, since infection of L. lovati to young sage grouse, Centrocercus urophasianus, could be detrimental to the bird populations in Nevada and Oregon in United States (Dunbar et al 2003), to understand the transmission cycle of this vector-borne bird disease should be investigated. Our previous study revealed that black flies distributed in the same area of Japanese rock ptarmigan habitat could be vector arthropods for L. lovati by detecting the same protozoa DNA sequence from the bodies of collected black flies (Sato et al 2009).…”
Section: Introductionmentioning
confidence: 99%